Crystal Structure and Thermodynamic Properties of Barium–Thulium Bismuthate with Perovskite Structure. Issue 6 (8th April 2013) - Bissengaliyeva, Mira R.; Knyazev, Alexander V.; Bekturganov, Nuraly S.; Gogol, Daniil B.; Taimassova, Shynar T.; Sukurov, Bolat M.; Smolenkov, Yuriy Y.; Tashuta, Galina N.; Vanderah, T.
<x xml:space="preserve">Abstract</x> A new sample of triple oxides—barium–thulium bismuthate Ba2TmBiO6 with perovskite structure—has been synthesized by ceramic technology. The unit cell parameters of the sample and the coefficients of thermal expansion have been determined by the method of X‐ray analysis. Thermal properties of the sample have been studied by DTA over the temperature range of 293–1473 K. The heat capacity of the compound has been measured over the range of 5–320 K by vacuum adiabatic calorimetry. Thermodynamic functions of the compound have been determined based on the heat capacity data.